A Butterfly‐Inspired Hierarchical Light‐Trapping Structure towards a High‐Performance Polarization‐Sensitive Perovskite Photodetector. (5th September 2019) - Zhan, Yan; Wang, Yang; Cheng, Qunfeng; Li, Chang; Li, Kaixuan; Li, Huizeng; Peng, Jingsong; Lu, Bo; Wang, Yu; Song, Yanlin; Jiang, Lei; Li, Mingzhu
Abstract: Extensive applications for photodetectors have led to demand for high‐responsivity polarization‐sensitive light detection. Inspired by the elaborate architecture of butterfly Papilio paris, a 1D nanograting bonded porous 2D photonic crystal perovskite photodetector (G‐PC‐PD) using a commercial DVD master and 2D crystalline colloidal arrays template was fabricated. The coupling effect from grating diffraction and reflection of the PC stopband renders the enhanced light harvesting of G‐PC‐PD. The porous scaffold and nanoimprinting process afford a highly crystalline perovskite film. White light responsivity and detectivity of G‐PC‐PD are up to 12.67 A W −1 and 3.22×10 13 Jones (6∼7 times that of a pristine perovskite photodetector). The highly ordered nanograting arrays of G‐PC‐PD enable polarization‐sensitive light detection with a rate of −0.72 nA deg −1 . This hierarchical perovskite integrated nanograting and 2D PC architecture opens a new avenue to high‐performance optoelectronic devices. Abstract : Die ausgeklügelte Architektur des Schmetterlingsflügels von Papilio paris diente als Inspiration für die Herstellung eines porösen photonischen 2D‐Perowskitphotodetektors mit 1D‐Nanogitter (G‐PC‐PD). Der Kopplungseffekt der Lichtbeugung am Gitter mit der Reflexion der PC‐Stoppbande führt zu einer verstärkten Lichternte, und das unidirektionale 1D‐Nanogitter ermöglicht die polarisationsempfindliche Lichtdetektion durch G‐PC‐PD.